Effect of sex steroids on colonic distension-induced delay of gastric emptying in rats - (:unkn) unknown (WILEY, 2004)
Background and Aim: The objective of the present study was to examine the effect of gonadal hormones on gastric motor response to non-noxious and noxious stimuli of colonic distension. Methods: Male Wistar albino rats were used. Under ketamine anesthesia some rats underwent castration (n = 24), while the rest of the rats were sham-operated (n = 67) and divided into different groups (n = 7-8 per group). On the 15th day of surgery, liquid gastric emptying studies were commenced. Results: Non-noxious (P < 0.05) or noxious (P < 0.01) colonic distension inhibited gastric emptying rate. Estradiol pretreatment (20 mug/kg per day, for 5 days, s.c.) inhibited gastric motility, while estradiol pretreatment or castration of the rats prior to noxious distension prevented the delay in gastric emptying. In contrast, blockade of testosterone receptors had no effect on the delay in gastric emptying induced by either modes of distension. Conclusions: The results suggest that sex steroids have a modulatory role on the feedback control of gastric motility induced by noxious colonic distension. (C) 2004 Blackwell Publishing Asia Pty Ltd.
Keywords: castration; cologastric reflex; sex steroids; viscerovisceral reflex; IRRITABLE-BOWEL-SYNDROME; COLORECTAL DISTENSION; MOTILITY; PERCEPTION; PREGNANCY; SYMPTOMS; PAIN